Integrating ChatGPT as a Learning Tool: Potential Benefits and Critical Considerations - Danilo Petrassi (Pensa MultiMedia, 2024)
This article examines the potential integration of OpenAI's ChatGPT into educational settings, with a particular focus on its capacity to enhance students' engagement in learning contexts. In order to investigate the potential of ChatGPT to deliver tailored educational content to diverse learning groups, structured interviews were conducted between different types of students and the chatbot. These interviews were designed to simulate hypothetical basic real-world educational interactions. While the outcomes indicate that ChatGPT is capable of adapting to a range of educational needs and styles, thereby facilitating more accessible and engaging learning experiences, however, a lot of limitations such as the lack of emotional intelligence and the potential to reduce critical thinking have been identified-underscoring the necessity for cautious integration and ongoing monitoring of AI technologies in education settings. The researcher proposes a balanced approach to AI integration, emphasizing the potential for synergy between AI tools and traditional learning methods.